Transcriptoma diferencial e mecanismos moleculares associados ao desenvolvimento dos sintomas da meleira do mamoeiro - Madroñero, Leidy Johana (2018)
The papaya sticky disease (PSD) severely affects the papaya crops in Brazil and México. PSD is associated with the combined infection of Papaya meleira virus (PMeV) and Papaya meleira virus 2 (PMeV2) (PMeV complex). Interestingly, PSD symptoms appear only after flowering. To understand the mechanisms involved in this phenomenon, the differential transcriptome of C. papaya inoculated with the PMeV complex was analyzed and resulted in the modulation of 633 and 88 genes in the pre- and post-flowering stages, respectively. At pre-flowering, functional analysis showed an up-regulation of genes related to defense and transport in parallel to the down-regulation of several genes coding to cell wall, leucine rich kinase receptors (RLK-LRR) and cell cycle proteins. Regarding the genes related to the defense pathways, it was observed the up-regulation of several genes involved in callose metabolism, detoxification of reactive oxygen species (ROS) and salicylic acid (AS) responsive genes, such as PR1, PR2, PR5 and WRKY. These results suggest the involvement of SA-mediated signaling in the tolerance of C. papaya to the symptom development at pre-flowering. Hence, the role of SA in the resistance to the PMeV complex was evaluated by the exogenous application of SA in PMeV complex inoculated plants and resulted in a tendency to decrease the viral loads of PMeV and PMeV2 in the SA-treated plants. However, at pre-flowering, the plants also accumulated transcripts encoding proteins involved in the metabolism of ethylene, UDP-glycosyltransferases (UGTs), and the protein-inhibitor of the Non-Expresser of Pathogenesis Related Gene 1 (NPR1) NPR1-I / NIM1 protein, whose components play an antagonistic role in the induction of SA-mediated defense genes. In addition, the decrease in SA-signaling appears to be accentuated during post-flowering, since it was observed the down-regulation of PR1 repression and the up-regulation BSMT1 and jasmonic acid (AJ) metabolism genes, which are also negative regulators in accumulation of SA. These results together suggest that SA-mediated defense pathways are likely involved in the delayed symptoms at pre-flowering, but the induction of their negative regulators impairs the full and long-lasting activation.